Apresentação do artigo técnico elaborado em 2023 por meio da IN Proeg nº 01/2023: explorando o potencial do laboratório virtual de controle de sistemas com VPython no ensino de engenharia: análise e perspectivas para o futuro - COTA, Yuri de Oliveira (2023)
This work focuses on the presentation of the article entitled “Exploring the potential of the virtual laboratory for systems control with VPython in engineering teaching: analysis and perspectives for the future”. The development of this article took place over the period from January 3 to May 16, 2023, coinciding with the execution of the research project called “Virtual control laboratory”. This project was supervised by professors Dr. Rafael Suzuki Bayma and Dr. Raphael Barros Teixeira, whose guidance was fundamental for the direction and success of the research. At the heart of this study is the creation of the virtual control laboratory, which was based on the Python programming language. Within this environment, virtual simulations were elaborated aimed at classic problems of the discipline of Control at UFPA - Campus Tucuruí. The challenges selected for this endeavor were the MAGLEV (Magnetic Levitator) and the AeroPêndulo. In these instan- ces, the systems were modeled, the control implemented and interactive interfaces created for communication with users. The primary objective of these efforts was to improve students’ understanding and abstraction in relation to the topics covered in these scenarios, providing a more dynamic and contextualized learning environment. At the end of this work, the modules were successfully developed, achieving full functionality that allows their distribution and execution in local environments. In this process, three-dimensional representations of the systems were created and a command interface was implemented that allows the adjustment of reference signals interactively.